2007
DOI: 10.1590/s0103-50532007000300023
|View full text |Cite
|
Sign up to set email alerts
|

Study of the inversion reaction of the lactonic fusion on eremanthine derivatives

Abstract: As α-metileno-γ-lactonas 4(15)-diidroeremantina (8), 4(15),9(10)-tetraidroeremantina (9), isoeremantina (10), acetato alílico Δ 1,10 (11), 1(R),10(R)-diidromiqueliolido (12) e 4α-hidróxi acetato alílico Δ 1,10 (13) foram sintetizadas a partir do produto natural abundante eremantina (1). Essas substâncias foram submetidas à reação de hidrólise com KOH aquoso e os sais carboxílicos dessas lactonas tiveram suas hidroxilas ativadas na posição C-6, pela formação dos respectivos mesilatos (MsCl, Et 3 N, THF ou DMSO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…There was also studied the synthesis of micheliolide, a naturally occurring substance initially isolated from Michelia compressa with relevant biological activity [165]. In the following subitems are described the sequences of reactions that were developed aiming to attain these objectives [150,[166][167][168][169][170] as well as the results of the study from the reactions of catalytic hydrogenation and methanol addition to α-methylene-γ-lactone of eremanthine derivatives [171]. 6.11.1.…”
Section: Study Of the Inversion Reaction Of The Lactonic Fusion On Ermentioning
confidence: 99%
See 4 more Smart Citations
“…There was also studied the synthesis of micheliolide, a naturally occurring substance initially isolated from Michelia compressa with relevant biological activity [165]. In the following subitems are described the sequences of reactions that were developed aiming to attain these objectives [150,[166][167][168][169][170] as well as the results of the study from the reactions of catalytic hydrogenation and methanol addition to α-methylene-γ-lactone of eremanthine derivatives [171]. 6.11.1.…”
Section: Study Of the Inversion Reaction Of The Lactonic Fusion On Ermentioning
confidence: 99%
“…On the other hand, treatment of iodohydrin 139 with MsCl and Et 3 N in dichloromethane, by the procedure of Crossland and Servis [173], generated a mixture of conjugate dienes 151 and 152 instead of the intermediate mesylate at C-9 position (150), which would be used in the next step of hydrogenolysis with NaBH 3 CN in HMPA by the procedure of Hutchins et al [174], aiming to obtain the target molecule 149. The author is disregarding in this review the preliminary results reported before about this reaction [166]. On that occasion this reaction was described in the following way: treatment of 139 with MsCl/Et 3 N/CH 2 b [170] c [171] g [171] c [171] a [170] c [171] e [168,169] d [170] f [168,169] is instantly converted to the final products of elimination (151 and 152).…”
Section: Study Of the Inversion Reaction Of The Lactonic Fusion On Ermentioning
confidence: 99%
See 3 more Smart Citations